Analisis Hubungan Kepribadian The Big Five Terhadap Manajemen Konflik Pada Taruna AAU Dengan Metode Korelasi - Sibarani, Jeffry Martahan; Suwito, Suwito; Holimin, Holimin (Akademi Angkatan Udara, 2022)
Abstract— Air Force Academy is in charge of organizing the first education of Indonesian Air Force voluntary officers. The implementation of education covers aspects of personality (40%), cognitive (30%) and ability (30%). The application of the results of the analysis of the big five personality relationship to conflict management with the correlation method can map the characteristics and attitudes of cadets in dealing with problems. The Big Five Personality is a personality theory that is divided into five dimensions: openness, conscientiousness, extraversion, agreeableness, and neuroticism. The big five theory or 'the big five' model is categorized as a general personality trait. The big five is a dynamic organization within the individual as a psychophysical system that determines his unique way of adapting to the environment besides the big five also explains the relationship between cognition, affect, and action. The big five is one of the personalities that can predict and explain a person's behavior. This approach can be used to assist the care system at the Air Force Academy in coaching cadets to minimize possible violations.